Anticonvulsant Effect of Ferula Assa-Foetida Oleo Gum Resin on Chemical and Amygdala-Kindled Rats - Bagheri, Seyyed Majid (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: In Iranian traditional medicine, Ferula assa-foetida oleo gum resin (asafoetida) have been used as anti-convulsant agents. AIMS: This study was designed to evaluate the anti-convulsant effect of asafoetida on chemical and amygdala -kindled rats. MATERIALS AND METHODS: In chemical model, rats received orally asafoetida at dose of 50 and 100 mg/kg 90 minutes prior to Pentylenetetrazol injection in dose of 35 mg/kg intraperitoneally (i.p.) and control group received normal saline. Convulsive behavior was recorded for 30 minutes. For amygdala kindle model, bipolar stimulating and monopolar recording electrodes were implanted stereotaxically. After kindling, the effect of asafoetida (50 and 100mg/kg) on after discharge duration, duration of stage 5 seizure and latency to the onset of bilateral forelimb clonuses was measured. RESULTS: Pretreatment animals with asafoetida significantly reduced the mean seizure stage during the 20 kindling injection of Pentylenetetrazol. Seizure parameters in amigdala kindle model improved in treatment animals at both dose 50 and 100 mg/kg. The number of stimulations in stage 3, 4, and 5 in asafoetida-treated rats at both doses significantly increased. CONCLUSIONS: These results showed that asafoetida could prevent seizure in both chemical and electrical kindling model and this effect may partially be related to the terpenoids compounds.